Detection, Prevention and Early Treatment of Cardiovascular Disease in the Community - Khair Anwar, Khalidatul; Askrening; Yustiari; Asmaidar; Nasrawati (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
Cardiovascular disease is a major health problem in the world. The rate of cardiovascular diseases accounts for the highest mortality when compared to infectious diseases. The main treatment is healthy living behavior and early detection of heart and vascular diseases. The service aims to improve people's knowledge and skills about prevention, early detection and handling of cardiovascular disease attacks. Service is carried out by two methods, namely 1) counseling with the target of health cadres, 2) cardiopulmonary resuscitation training. The results of the service showed that health education was able to increase knowledge about cardiovascular diseases (P=0.000) and all participants were able to carry out cardiopulmonary resuscitation correctly.